Growing up in Europe’s backyard: researching on education and youth in Portuguese poor suburban settings - Silva, S. M.; Abrantes, P. (Second International Handbook of Urban Education, 2017)
This second handbook offers all new content in which readers will find a thoughtful and measured interrogation of significant contemporary thinking and practice in urban education. Each chapter reflects contemporary cutting-edge issues in urban education as defined by their local context. One important theme that runs throughout this handbook is how urban is defined, and under what conditions the marginalized are served by the schools they attend. Schooling continues to hold a special place both as a means to achieve social mobility and as a mechanism for supporting the economy of nations. This second handbook focuses on factors such as social stratification, segmentation, segregation, racialization, urbanization, class formation and maintenance, and patriarchy. The central concern is to explore how equity plays out for those traditionally marginalized in urban schools in different locations around the globe. Researchers will find an analysis framework that will make the current practice and outcomes of urban education, and their alternatives, more transparent, and in turn this will lead to solutions that can help improve the life-options for students historically underserved by urban schools.